2008
DOI: 10.1109/tmi.2007.911492
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and Statistical Bounds for Three-Dimensional Polar Shapes in Diffuse Optical Tomography

Abstract: Voxel-based reconstructions in Diffuse Optical Tomography (DOT) tend to produce very smooth images due to the attenuation of information of high spatial frequency. This then causes difficulty in estimating the spatial extent and contrast of anomalous regions such as tumors. Given an assumption that the target image is piecewise constant, we can employ a parametric model to estimate the boundaries and contrast of an inhomogeneity directly. In this paper, we describe a method to directly reconstruct such a shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In Ref. 26, regularization was achieved by reparameterizing the problem using a spherical harmonic basis, which reduced the number of unknowns to be estimated from the data to an object center position and various shape parameters. The CRLB for the shape parameters was subsequently computed and used to provide confidence limits for the shape estimates.…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. 26, regularization was achieved by reparameterizing the problem using a spherical harmonic basis, which reduced the number of unknowns to be estimated from the data to an object center position and various shape parameters. The CRLB for the shape parameters was subsequently computed and used to provide confidence limits for the shape estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the CRB can be used to describe and predict the asymptotic behavior of the ML estimator. Finally, the derivation and the computation of the CRB are often easier than the ones associated to other performance bounds, which makes this bound attractive in various fields [8][9][10][11][12][13]. In the particular context of inverse scattering, the CRB has gained a significant interest recently.…”
Section: Introductionmentioning
confidence: 99%
“…Using a level-set technique for image reconstruction, Schweiger et al [ 8 ] showed that detection and localization of small objects could be improved in 3D. Boverman et al [ 9 ] used a parametric approach to reconstruct shape and contrast of piece-wise constant regions in 3D with spherical harmonics for modeling sharp boundaries in tissue and demonstrated quantitative results in a domain with a single inclusion. Zacharopoulos et al [ 10 ] used a similar strategy and showed that they could accurately recover location and contrast of an anomaly in experiments on a domain with single inclusion.…”
Section: Introductionmentioning
confidence: 99%